FAKTOR-FAKTOR YANG MEMENGARUHI NIAT DAN PERILAKU WHISTLEBLOWING MAHASISWA AKUNTANSI - Parianti, Ni Putu Ika; Suartana, I Wayan; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
This study aimed to analyze the influence of the factors contained in Theory of Planned Behavior are the attitude toward the behavior, subjective norms, and perceived behavioral control on whistleblowing intention and behavior. Specifically, the primary purposes of this study is to examines: (1) influence of attitude toward the behavior on whistleblowing intention, (2) influence of subjective norm on whistleblowing in ten tion, and (3) influence of perceived behavioral control on whistleblowing intention, (4) influence of perceived behavioral control on whistleblowing behavior and (5) influence of whistleblowing intention on whistleblowing behavior. This study conducted with survey method by distributing questionnaires to accounting studen’s Udayana University. The population of this study is 380 accounting student s. The sampling method is purposive sampling . The sampling of this study is 175 accounting student . The questionnaire can be used as many as 116 questionnaires. Data analysis is done by path analysis model. The results showed that attitudes toward behavior, subjective norm  and perceived behavioral control have positive effect  on whistleblowing intention. Whistleblowing intention and perceived behavioral control have positive effect  on whistleblowing behavior.
Keywords: whistleblowing, fraud, theory of planned behavior